2018
DOI: 10.1029/2018ms001276
|View full text |Cite
|
Sign up to set email alerts
|

Computational Benefit of GPU Optimization for the Atmospheric Chemistry Modeling

Abstract: Global chemistry-climate models are computationally burdened as the chemical mechanisms become more complex and realistic. Optimization for graphics processing units (GPU) may make longer global simulation with regional detail possible, but limited study has been done to explore the potential benefit for the atmospheric chemistry modeling. Hence, in this study, the second-order Rosenbrock solver of the chemistry module of CAM4-Chem is ported to the GPU to gauge potential speed-up. We find that on the CPU, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Therefore, it is possible to achieve massive parallelism for a parameterization by carefully restructuring the code and increasing the number of columns (for a global model, this means increasing the horizontal resolution), which then becomes a natural fit for GPU computing (Sun et al, 2018).…”
Section: Gpu Directivesmentioning
confidence: 99%
“…Therefore, it is possible to achieve massive parallelism for a parameterization by carefully restructuring the code and increasing the number of columns (for a global model, this means increasing the horizontal resolution), which then becomes a natural fit for GPU computing (Sun et al, 2018).…”
Section: Gpu Directivesmentioning
confidence: 99%
“…For example, the Community Earth System Model version 2 (CESM2; Danabasoglu et al, 2020) has been shown to have a higher supercooled liquid fraction than observed (Gettelman et al, 2020), which has been linked to a higher climate sensitivity than previous versions (Gettelman et al, 2019b). In addition, cloud microphysics controls the formation of precipitation, which is often too light and too frequent in large-scale weather and climate models (Stephens et al, 2010). This frequency bias has been shown to be directly attributable to cloud microphysics (Gettelman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Progress has been made to accelerate weather, climate and atmospheric-chemistry models with general purpose graphics processing units (GPUs) (Yashiro et al, 2016;Alvanos and Christoudias, 2017;Sun et al, 2018;Fuhrer et al, 2018;Müller et al, 2019), but a wider utilisation is pending. Other high performance computing applications such as lattice quantum chromodynamics with typically smaller codebase and less legacy code swiftly exploited the computational resources of GPUs (Egri et al, 2007;Clark et al, 2010).…”
Section: Introductionmentioning
confidence: 99%